Dilema Eksistensi Tokoh Rin Dalam Anime Usagi Drop Menurut Teori Kepribadian Marxian Erich Fromm: The Existential Dilemma of Rin in the Anime Usagi Drop According to Erich Fromm's Marxian Personality Theory - Meizora, Tiara; Radoti, Nathania Valmai; Wulandari (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
This study aims to analyze and describe the existential dilemma experienced by the character Rin in the anime Usagi Drop. This study uses the study of Erich Fromm's existential dilemma theory. The technique used in collecting data was note-taking and the data obtained was analyzed using a qualitative descriptive method. The results of the research show the existential dilemma experienced by Rin's character who lives a new life after losing his father. The existential dilemma experienced by Rin's character is; 1) humans as animals and as humans who are shown by Rin's awareness of her physical needs but also have the nature of attention and affection for Daikichi characters, 2) life and death which are shown by Rin's fear of death but at the same time she is also aware of the coming of death someday, 3) imperfection and perfection in the form of awareness of the strengths and weaknesses that she has, 4) solitude and togetherness shown by Rin's independent attitude in living life but at the same time she also needs Daikichi's help.